The Intersection of Behavioral Science and Digital Health: The Case for Academic–Industry Partnerships. (February 2019) - Hingle, Melanie; Patrick, Heather; Sacher, Paul M.; Sweet, Cynthia Castro
A decade after the first health app became available, the field of digital health has produced a range of health behavior insights and an expanding product portfolio. Despite sustained interest and growth fueled by academic and industry interests, the impact of digital health on health behavior change and related outcomes has been limited. This underperformance relative to expectations may be partially attributed to a gap between industry and academia in which both seek to develop technology-driven solutions but fail to converge around respective, unique strengths. An opportunity exists for new and improved collaborative models of research, innovation, and care delivery that disrupt the field of behavioral medicine and benefit academic and industry interests. For those partnerships to thrive, recognizing key differences between academic and industry roles may help smooth the path. Here we speak specifically to concerns particular to academics and offer suggestions for how to navigate related challenges.